Recurrent ruptured ectopic pregnancy: a case report - Pramana, Cipta; Angelina, Alicia; Hilwa, Najwa Sufa; Munandar, Avicennia Nandira; Lukas, Ario; Hosein, Ivan (International Surgery Journal, 2020)
Ruptured ectopic pregnancy is an emergency obstetric case which requires fast and correct management. Authors report an interesting case of a 27-years-old with recurrent ruptured ectopic pregnancy and underwent a laparoscopy and salpingostomy operation. The operation outcome was good with no perioperative complications and operating results. Ectopic pregnancy requires fast and correct management because this case is an emergency and can lead to mortality.